Effect of mitomycin C on X‐ray repair cross complementing group 1 expression and consequent cytotoxicity regulation in human gastric cancer cells. Issue 5 (6th January 2019) - Tung, Shui‐Yi; Lin, Chien‐Tsong; Chen, Cheng‐Nan; Huang, Wen‐Shih
Abstract: Gastric cancer is the fourth most common cancer and ranks as the second leading cause of cancer‐related deaths across the world. The combination therapy of surgery with chemotherapeutic drugs, that is, mitomycin C (MMC), is becoming a major strategy for patients with advanced gastric cancer. However, drug resistance is a major factor that limits the effectiveness of chemotherapy, which ultimately leads to the failure of cancer chemotherapy. X‐ray repair cross complementing group 1 (XRCC1), a scaffold protein of the base excision repair process, has been implicated in the development of tumor chemoresistance. Thus, this study aimed to explore whether XRCC1 expression could be regulated, its role in gastric AGS cancer cells treated with MMC, and the underlying mechanism. The results of this study demonstrate that XRCC1 expression could be upregulated in AGS cells treated with MMC, and this upregulation could subsequently reduce the cytotoxicity of MMC in AGS cells. Furthermore, MMC‐upregulated XRCC1 expression was regulated by MAPK signaling through activating the transcription factor Sp1. These results indicate the role of XRCC1 in the development of drug resistance to MMC in gastric AGS cells. Elucidating the mechanism concerning the MAPKs and transcription factor Sp1 may provide another notion for the development of a clinical chemotherapy strategy for gastric cancers in the future. Abstract : This study indicates the role of X‐ray repair cross complementing group 1 (XRCC1) in the development of drug resistance to mitomycin C (MMC) in gastric AGS cells. Elucidating the mechanism underlying the MAPKs and transcription factor Sp1 may provide another notion for the development of a clinical chemotherapy strategy for gastric cancers in the future.